Agricultural Foreign Trade Development. (Quezon City Agricultural Marketing Statistics Analysis Division, Bureau of Agricultural Statistics, 1987)
Presents the revised version of the monthly report on agricultural foreign trade statistics. The report features statistics on major agricultural exports and imports in simplified format. Farm product imports are commodity specific, instead of being lumped under the usual commodity groupings.
Monthly